Sekolah sebagai Ruang Sosialisasi dan Screening Moral: Kajian Konseptual Pendidikan Islam dalam Pembentukan Karakter Anak - Farah Qotrun Nada; Nur Khasanah (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Schools as formal educational institutions have a strategic function in shaping children's character through the socialization of moral values and behavioral screening, which emphasizes the holistic internalization of Islamic values. This study uses a conceptual approach to analyze how schools play a role in shaping character, assessing students' moral behavior, and working with families as educational partners. The results of the study show that the integration of Islamic value-based character education, the moral evaluation process by teachers, and family involvement in reinforcing values at home creates a comprehensive moral ecosystem. Schools become arenas for moral learning experiences, where children learn to evaluate their own actions, understand social consequences, and consistently internalize ethical values. This entire process prepares children to become individuals who are not only academically intelligent, but also morally mature, socially responsible, and highly spiritually aware. These findings emphasize the importance of synergy between schools, teachers, and families to support the formation of sustainable Islamic character